MXene-based materials for enhanced water quality: Advances in remediation strategies - Ali Mohammad Amani; Milad Abbasi; Atena Najdian; Farzaneh Mohamadpour; Seyed Reza Kasaee; Hesam Kamyab; Shreeshivadasan Chelliapan; Mostafa Shafiee; Lobat Tayebi; Ahmad Vaez; Atefeh Najafian; Ehsan Vafa; et al. (Ecotoxicology and Environmental Safety)
Two-dimensional MXenes are promising candidates for water treatment because of their large surface area (e.g., exceeding 1000 m²/g for certain structures), high electrical conductivity (e.g., >1000 S/m), hydrophilicity, and chemical stability. Their strong sorption selectivity and effective reduction capacity, exemplified by heavy metal adsorption efficiencies exceeding 95 % in several studies, coupled with facile surface modification, make them suitable for removing diverse contaminants. Applications include the removal of heavy metals (e.g., achieving >90 % removal of Pb(II)), dye removal (e.g., demonstrating >80 % removal of methylene blue), and radioactive waste elimination. Furthermore, 3D MXene architecture exhibit enhanced performance in antibacterial activities (e.g., against bacteria), desalination rejection percentage, and photocatalytic degradation of organic contaminants. However, several challenges have remained, which necessitate further investigation into toxicity (e.g., assessing effects on aquatic organisms), scalability, and cost-effectiveness of large-scale production. This review summarizes recent advancements in 3D MXene-based functional materials for wastewater treatment and water remediation, critically analyzing their both potential and limitations.